Surgical management of garre's osteomyelitis in an 8-year-old child - Lida Mary Nidhin Philip; Francis Akkara; Tahura Khwaja; Taradevi Narayan; Akshata G Kamath; Nidhin Philip Jose (Wolters Kluwer Medknow Publications, 2021)
Chronic non-suppurative osteomyelitis, also known as Garre's osteomyelitis is a well-described pathologic entity in dental literature. We present here a case report of a unilateral hard bony swelling of the lower jaw associated with infection. Radiograph revealed the pathognomic feature of 'onion skin' appearance. Surgical recontouring of the lower jaw was performed since there was no evidence of bone remodelling after removal of the infected tooth.